Pioglitazone Ameliorates Lipid Metabolic Disorder in KKAy Mice - Sifan Chen,; Qing Wei,; Yanshuang Sun,; Xincai Xiao,; Zili Zhang,; Liangru Ke,; Niman Zhou,; Zhiming Shan,; Xiang Feng,; Wei Zhu, (Journal of Pharmacy and Nutrition Sciences, 2011)
Pioglitazone (pio) has been used as an effective hypoglycemic drug in medicine, however, the effects and mechanisms of pio on lipid metabolic disorder are still largely unknown. To explore the effects of pio on serum and liver lipid level and antioxidant ability of mice with lipid metabolic disorder, KKAy mice were treated with piofor 12 weeks and their lipid and antioxidant indices were compared to those of KKAy mice without pio treatment. C57BL/6J mice were used as control animals. The results show that pio treatment reduces serum and liver TG, elevates serum HDL-C level, increases serum and liver SOD activity, attenuates serum MDA content, ameliorates liver steatosis, induces liver PPARγexpression and enhances AMPKα phosphorylation level. In conclusion, the results indicate that pio could regulate blood lipid level, reduce liver lipid deposition and enhance antioxidant capacity of mice with lipid metabolic disorder, which is possibly through increasing AMPKα phosphorylation.